The Isomerization of Triphenylmethyl Isocyanide: Evidence for a Cationic Chain Mechanism in Polar Solvents - Michael Meier; Christoph Rüchardt (CHIMIA)
Triphenylmethyl isocyanide (1) isomerizes to triphenylmethyl cyanide (2) in non-polar solvents at 200-250 °C by a sigmatropic 1,2-rearrangement. To account for the high rate of rearrangement in polar solvents (e.g. acetonitrile) at 60-80°C, a cationic chain mechanism is proposed in contrast to the ion pair return mechanism discussed in the literature.